Analysis of the Role of Tourism Awareness Group Communication in Developing Tourism Destinations Based on Local Wisdom in Tipang Village, Baktiraja District, Humbang Hasundutan Regency, North Sumatra Province - Sibarani, Halasan Sugianto; Humaizi, Humaizi; Kurniawati, Dewi (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2024)
This research aims to analyze the communication role of the tourism awareness group in Tipang village by prioritizing local wisdom in developing tourism destinations, analyzing the strategies of tourism awareness groups applied in developing tourism destinations, and finding the obstacles experienced by tourism awareness groups in developing tourism destinations based on local wisdom. This research uses a descriptive qualitative approach with a phenomenological paradigm. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The validity of the data was checked by triangulating interviews with the Lake Toba Authority Implementing Agency (BPODT) and academics who had carried out tourism development activities at the research location. This research found that 1) The communication role of the Tipang village tourism awareness group has three types of roles: active role, participatory role, and passive role.2) Strategy of tourism awareness groups in developing tourism destinations based on local wisdomTipang village implements an integration strategy by involving other tourism destination managers, utilizing information dissemination through social media and print media distributed in strategic areas or places